0888 Depression in African Americans with Obstructive Sleep Apnea. (12th April 2019) - Olanipekun, Titilope; Abe, Temidayo; Nwokike, Chuckwuemeka; Bakinde, Nicolas; Fotzeu, Claudia; Clark, Kyra
Abstract: Introduction: Obstructive sleep apnea (OSA) is often associated with depression. Identifying and treating depression improve the quality of life of patients with OSA. African Americans (AA) tend to have severe OSA and poor access to care. OSA management in the primary care setting has recently gained traction to improve outcomes. There is a paucity of data on depression screening and prevalence in African American patients with OSA Methods: We conducted a retrospective study of all AA patients with a diagnosis of OSA (ICD-9 code 327.23), who visited the primary care sleep clinic of Grady Memorial Hospital between December 2017 and November 2018. We examined their medical records for depression screening using the patient health questionnaire (PHQ-9). The PHQ-9 scored from 0-27 is a validated depression screening tool in primary care settings. PHQ-9 score ≥ 10 has a sensitivity and specificity > 85% for major depressive disorder (MDD). Scores of at least 5, 10, 15, and 20 represent mild, moderate, moderately severe and severe depression respectively. We adjusted for patients' co-morbidities in the analysis. Statistical analysis was conducted using STATA 14. Results: 216 AA patients with OSA were identified. The average (±SD) age was 55 years (± 9.3). 60% of patients were females. 201 patients were screened for depression using PHQ-9 out of which 19% were diagnosed with at least mild depression and 14% with MDD. The prevalence of depression was higher in females (69%, P< 0.005) and patients 50 years and older (80%, P< 0.005). Higher odds of MDD were seen in females (AOR 2.06, CI 1.41 - 4.76), patients aged ≥ 50 years (AOR 1.67, CI 1.09 - 3.55), and patients with ≥ 4 co-morbidities (AOR 1.88, CI 1.24 - 3.61) Conclusion: Our study demonstrated that the prevalence rate of MDD in AA patients with OSA managed in the primary care clinic was 14%. Female sex, older age (≥ 50 years) and multiple co-morbidities (≥4) were associated with an increased likelihood of MDD. Future studies should evaluate the appropriate linkage of these patients to mental health care Support (If Any): -